Smartphone data as an electronic biomarker of illness activity in bipolar disorder. (23rd September 2015) - Faurholt‐Jepsen, Maria; Vinberg, Maj; Frost, Mads; Christensen, Ellen Margrethe; Bardram, Jakob E; Kessing, Lars Vedel
Abstract : Objectives: Objective methods are lacking for continuous monitoring of illness activity in bipolar disorder. Smartphones offer unique opportunities for continuous monitoring and automatic collection of real‐time data. The objectives of the paper were to test the hypotheses that (i) daily electronic self‐monitored data and (ii) automatically generated objective data collected using smartphones correlate with clinical ratings of depressive and manic symptoms in patients with bipolar disorder. Methods: Software for smartphones (the MONARCA I system) that collects automatically generated objective data and self‐monitored data on illness activity in patients with bipolar disorder was developed by the authors. A total of 61 patients aged 18–60 years and with a diagnosis of bipolar disorder according to ICD‐10 used the MONARCA I system for six months. Depressive and manic symptoms were assessed monthly using the Hamilton Depression Rating Scale 17‐item (HDRS‐17) and the Young Mania Rating Scale (YMRS), respectively. Data are representative of over 400 clinical ratings. Analyses were computed using linear mixed‐effect regression models allowing for both between individual variation and within individual variation over time. Results: Analyses showed significant positive correlations between the duration of incoming and outgoing calls/day and scores on the HDRS‐17, and significant positive correlations between the number and duration of incoming calls/day and scores on the YMRS; the number of and duration of outgoing calls/day and scores on the YMRS; and the number of outgoing text messages/day and scores on the YMRS. Analyses showed significant negative correlations between self‐monitored data (i.e., mood and activity) and scores on the HDRS‐17, and significant positive correlations between self‐monitored data (i.e., mood and activity) and scores on the YMRS. Finally, the automatically generated objective data were able to discriminate between affective states. Conclusions: Automatically generated objective data and self‐monitored data collected using smartphones correlate with clinically rated depressive and manic symptoms and differ between affective states in patients with bipolar disorder. Smartphone apps represent an easy and objective way to monitor illness activity with real‐time data in bipolar disorder and may serve as an electronic biomarker of illness activity.